Tsinghua Science Park : a source of Chinese entrepreneurial innovation - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
With long willows and new cicada, blowing in the gentle breeze and rain in the early summer of 2014, Tsinghua Science Park, located just outside the East Gate of Tsinghua University, was filled with vibrant green colours. 20 years ago in the same place, were crumbling tenements, abandoned railways and small township enterprises, such as tyre and popsicle factories. Now, it is a centre for R&D headquarters of multinational companies, as well as headquarters of Chinese technology companies and other venture enterprises. As Tsinghua Science Park began to celebrate its 20th anniversary in August 2014, Mei Meng, Chairman of Tus-Holdings and founder of the Tsinghua Science Park, was actively preparing his team for the celebration.